Public relations strategy of Tarumajaya Village in developing promotion and local potentials - Sjuchro, Dian Wardiana; Surachman, Akhmad Yani; Nugraha, Aat Ruchiat; Viannisa, Nadhifa (Universitas Padjadjaran, 2024)
Background: The role of the community in introducing, communicating, or promoting Tarumajaya Tourism Village to the wider community outside is vital. Community Information Group (KIM) Cerdas Tarumajaya has a strategic role in connecting local communities with tourism and developing the tourism potential of Tarumajaya Village and the visibility of Tarumajaya as a leading tourist destination. Purpose: This study examined how KIM Cerdas Tarumajaya as public relations implemented strategies to enhance local potential and promote Tarumajaya as a leading tourist destination, and why these strategies were used. Methods: This study used a case study approach. Results: The communication and promotion of Tarumajaya tourism village cover the campaign for Tarumajaya as a whole tourist destination and a highlight for each attraction within the village, such as Situ Cisanti, Kilometre 0 Citarum, Paesan Hill, Pakawa Pine Forest, and Tawides. Every tourism site wants to be communicated and marketed simultaneously. Furthermore, the communication and promotion do not emphasise the differences between one tourist attraction and another. However, regardless of the achievement, the social media management of Tarumajaya Tourism Village is less consistent. Conclusion: Tarumajaya Tourism Village’s communication and promotion lack concentration and consistency. Implications: The success of communication and promotion depends on tourism differentiation, communication messages, and the consistency of information handling.